2012
DOI: 10.1590/s0103-50532012005000052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of LaNiO3 perovskite by the modified proteic gel method and study of catalytic properties in the syngas production

Abstract: Este trabalho descreve um estudo sobre a síntese da perovsquita LaNiO 3 via método do gel proteico, variando quantidade de colágeno e sobre a atividade catalítica de LaNiO 3 e LaNiO 3 /Al 2 O 3 na produção de gás de síntese (CO + H 2 ). Os padrões de difração de raios X revelaram a formação da estrutura perovsquita em todas as amostras preparadas pelo método de síntese do gel protéico, variando a quantidade de colágeno e após calcinações a 700 ºC por 2 h. O catalisador LaNiO 3 /Al 2 O 3 preparado pelo método d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It is possible to observe that even at 900 ºC, the sample still show a mass loss, which can be attributed to the decomposition of carbonates formed [17]. It was possible to observe a slight mass gain above 670 and 830 °C in the samples LN-3 and L7S3N-3, respectively, due to the oxidation reactions, as observed in other studies for perovskite of nickel-based synthesis [16,17]. Fig.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…It is possible to observe that even at 900 ºC, the sample still show a mass loss, which can be attributed to the decomposition of carbonates formed [17]. It was possible to observe a slight mass gain above 670 and 830 °C in the samples LN-3 and L7S3N-3, respectively, due to the oxidation reactions, as observed in other studies for perovskite of nickel-based synthesis [16,17]. Fig.…”
Section: Resultssupporting
confidence: 72%
“…The method is distinguished by its simplicity and ability to obtain crystalline materials with high purity and good stoichiometric control. It is an alternative route to obtain oxides with high efficiency and low cost [16]. Researchers showed that it is possible to obtain perovskites through the collagen-modified proteic gel method with formation of a single-phase material at 700 ºC [6,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, LaNiO3 is a promising candidate as an electrode constituent material due to excellent electrical properties [1][2][3]. Additionally, LaNiO3 and its derived materials have been used as catalysts because they show high catalytic activity in several chemical reactions, such as the evolution of hydrogen gas from organic compounds [4][5][6][7][8]. Particularly, the visible-light-driven photocatalytic activity of LaNiO3 has lately received particular attention in the degradation of organic compounds [9][10][11] and hydrogen production [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…LaNiO3 has been synthesized using various techniques, such as sol-gel [5,10,12,13], combustion [1,6,8,9,[14][15][16][17], hydrothermal [7,18], microwave heating [19], spray pyrolysis [4], reverse microemulsion [11], polymerization [20], and molten salt [21].…”
Section: Introductionmentioning
confidence: 99%